Universal design and social responsibility: towards a sustainable built environment - Abdul Rahim, Asiah; Mohd Yaacob, Naziaty; Abd. Samad, Nur Amirah; Tukiman, Izawati (2015)
The objectives of this paper are firstly to highlight the importance of Universal Design and Social Responsibility, secondly an overview of important factors to consider in providing for accessible transportation and finally to review and introduce the application of Universal Design from Malaysian experience. Universal Design and Social Responsibility are tightly related in terms of its core subjects such as Human Rights such as discrimination of People with Disabilities (PwDs) and vulnerable groups; economic, social and cultural rights; consumer issues such as access to essential services, education and awareness of community involvement and development such as technology development and access as well as social investment. Consideration of providing accessible transportation constitutes the important factors for Universal Design access features such as routes, entrances, toilets, emergency exits and wayfinding, and services provision such as customer assistance, guides and assistive devices. Stating the history of the application of Universal Design in Malaysia, Malaysia gain independence in 1957 and in the late 1980s, the development of Malaysian Standards and code of practices on access for the disabled was initiated and later revised Malaysian Standard of MS 1184:2014; Universal Design and Accessibility in the Built Environment-Code of Practice for the public in 2014. In conclusion universal design is a very important consideration for a sustainable built environment.